REVIEW ARTICLE : IDENTIFICATION OF OFFICE BUILDING FACESADES AS A FORM OF BUILDING IN A TROPICAL CLIMATE AT JENDRAL SUDIRMAN PADANG - Friyessi, Friyessi; Andi, Andi (Journal of Scientech Research and Development, 2024)
Building facades are not just an attractive appearance, but also play a crucial role in creating indoor thermal comfort, especially in tropical areas like Padang. This research analyzes the facade designs of several offices on Jalan Jenderal Sudirman to see their effect on thermal comfort. The factors studied include building orientation, facade openings, and the use of shading or vegetation elements. Proper building orientation, optimal facade openings, and use Effective shading elements are key to achieving thermal comfort. This research analyzes the facade designs of several offices on Jalan Jenderal Sudirman, Padang, to see their effect on indoor thermal comfort. The tropical climate in Padang is a challenge in creating a comfortable space. Research results show that facade designs that follow tropical building standards can reduce energy consumption and increase occupant comfort. Natural ventilation also plays an important role in achieving thermal comfort. So it can be concluded that the design and shape of the facade will follow the orientation of the building. This research suggests that factors such as orientation, openings and shading should be given more attention in building design, especially in tropical areas. The results of the research show that the facade design of several buildings on Jalan Jenderal Sudirman is considered quite good and suitable for tropical climates. The shape of the facades on the buildings it is not only a matter of aesthetics, but also greatly influences the comfort and energy efficiency of buildings, especially in tropical climates.